Kinetic studies of novel inhibitors of endomorphin degrading enzymes - Perlikowska, Renata (Springer-Verlag, 2011)
Endomorphins (EMs), two endogenous μ-opioid receptor selective ligands, are attractive lead compounds for opioid-based pain management studies. However, these peptides are quickly degraded by peptidases, in particular by dipeptidylpeptidase IV (DPP IV) and aminopeptidase M (APM). Targeting enzymatic degradation is one approach to prolong endomorphin activity. In this study we characterized the action of two new inhibitors of similar to endomorphins structure, Tyr-Pro-Ala-NH(2) (EMDB-2) and Tyr-Pro-Ala-OH (EMDB-3), which were designed earlier in our laboratory. The presented data give evidence that EMDB-2 and EMDB-3 are potent inhibitors of enzymes responsible for endomorphin cleavage. These compounds are stable and easily synthesized. EMDB-2 and EMDB-3 are competitive inhibitors of both, DPP IV and APM, with K (i) values in micromolar range. They are less potent than diprotin A in protecting EMs against DPP IV but more potent than actinonin in protecting these peptides against APM.